In-vivo continuous monitoring with biosensors based on engineered biological recognition elements: opportunities and challenges - Nagata, Madoka; Sode, Koji (Frontiers in Sensors, 2025)
The biosensors are generally described as analytical devices that transduce a signal derived from molecular recognition by biological recognition element (BRE) to quantify analytes or species in samples by combining varieties of transducers with different detection modalities. Therefore, the characteristics of biosensors are highly dependent on BREs. BREs are categorized into two types; a biocatalytic type BRE (BioCat-BREs) and a bioaffinity type BRE (BioAff-BREs). Following the currently most successful biosensors, the sensors for continuous glucose monitors (CGMs) for diabetes management, the development of biosensors for continuous sensing of biomarkers and drugs, such as small molecule drugs, peptides and proteins such as therapeutic antibodies is of increasing interest to both researchers and clinicians. However, unlike glucose oxidoreductases and the concentration of glucose in the mM range, the target molecules for the future continuous monitoring system require the development of innovative BioCat-BREs, which ideally are direct transfer type oxidoreductases, and BioAff-BREs which maintain their high affinity and specificity to the target while their binding site is regenerable under in vivo sensor operating condition, as well as the development of new modalities and devices to detect targets in the µM - pM range.